2002
DOI: 10.1210/jcem.87.3.8354
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Status Correlates with the Calcium Content of Coronary Atherosclerotic Plaques in Women

Abstract: Estrogen status is associated with coronary calcium and plaque area independent of age and CHD risk factors. Estrogen may modulate the calcium content of atherosclerotic plaques, as well as plaque area and may slow the progression of atherosclerosis in women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
14
0
2

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(18 citation statements)
references
References 36 publications
2
14
0
2
Order By: Relevance
“…It is likely that the Runx2 and BMP2 regulatory cascades play a crucial role in vascular OPN expression at later stages of calcific vasculopathy (71), i.e. once the progressive, osteogenic regulation of macrovascular calcification has been established as a consequence of responses to initial metabolic or inflammatory insults (20,(71)(72)(73). However, we identified that the OPN promoter regions required for Smad responses (Ϫ220 to Ϫ190) and Runx2:Ets recognition (Ϫ134 to Ϫ129; Ϫ118 to Ϫ113) in osteoblasts are not required for basal or glucose-regulated OPN promoter activity in A7r5 aortic VSMCs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is likely that the Runx2 and BMP2 regulatory cascades play a crucial role in vascular OPN expression at later stages of calcific vasculopathy (71), i.e. once the progressive, osteogenic regulation of macrovascular calcification has been established as a consequence of responses to initial metabolic or inflammatory insults (20,(71)(72)(73). However, we identified that the OPN promoter regions required for Smad responses (Ϫ220 to Ϫ190) and Runx2:Ets recognition (Ϫ134 to Ϫ129; Ϫ118 to Ϫ113) in osteoblasts are not required for basal or glucose-regulated OPN promoter activity in A7r5 aortic VSMCs.…”
Section: Discussionmentioning
confidence: 99%
“…Lanes 1,4,7,10,13,16,19,22,25, and 28, basal binding. Lanes 2,5,8,11,14,17,20,23,26, and 29, binding in the presence of the indicated antibody. Note that the anti-USF1 antibody (lane 26) markedly diminished formation of this protein-DNA complex.…”
Section: A7r5 Aortic Vsmc Dna Binding Activities Containing C-fos C-mentioning
confidence: 99%
See 1 more Smart Citation
“…26,27 In the context of atherosclerosis, studies support a protective effect of E2 on plaque calcification in women, based on the cardiovascular protective effects of E2 that reduce total plaque burden, attributable to modulation of traditional risk factors, such as plasma high-density lipoprotein and low-density lipoprotein. 28,29 In the clinic, studies show low serum E2 levels associate with increased coronary artery calcification (CAC), [30][31][32] whereas E2 replacement in younger menopausal women reduces CAC. 33,34 These findings are supported by animal studies that show E2 protects against atherosclerotic plaque calcification when associated with beneficial effects on plaque progression.…”
mentioning
confidence: 99%
“…De multiples études in vitro et in vivo chez l'animal et chez l'homme, supportent une multitude de données relatives à l'action vasculaire des estrogènes, dont on peut retrouver les points les plus importants dans plusieurs revues [14][15][16]. Dans les vaisseaux non lésés, et par l'interaction avec les divers types de récep-teurs des estrogènes, on obtient sous l'effet de ceux-ci une vasodilatation ( NO, prostacyclines) et une diminution des dépôts lipidiques, une diminution de la progression --et même une reduction --de l'athérogenèse, ainsi qu'une diminution de la précipitation de calcium au niveau des plaques [17] et enfin une réduction bénéfique de l'activation des processus inflammatoires au cours des stades précoces de l'athérogenèse [18]. Dans les vaisseaux lésés, la capacité de liaison aux récepteurs estrogéniques, la production de NO et de prostacycline, et la vasodilatation sont ineffectives, l'activation inflammatoire est accrue et l'instabilité des plaques augmente, accroissant ainsi le risque artériel.…”
Section: Discussionunclassified